ON ONE CLASS OF MUTUALLY INVERSE PARTITION POLYNOMIALS - Гой, Тарас Петрович; Заторський, Роман Андрійович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
We study a class of mutually inverse partition polynomials, which are represented as a functions of some triangular matrices.